Relationship between European eel Anguilla anguilla infection with non‐native parasites and swimming behaviour on encountering accelerating flow. Issue 5 (20th March 2015) - Newbold, L. R.; Hockley, F. A.; Williams, C. F.; Cable, J.; Reading, A. J.; Auchterlonie, N.; Kemp, P. S.
<x xml:space="preserve">Abstract</x> The effect of Anguillicola crassus, Pseudodactylogyrus bini and Pseudodactylogyrus anguillae infection on the behaviour of downstream migrating adult European eels Anguilla anguilla as they encountered accelerating water velocity, common at engineered structures where flow is constricted (e.g. weirs and bypass systems), was evaluated in an experimental flume. The probability of reacting to, and rejecting, the velocity gradient was positively related to A. crassus larval, adult and total abundance. High abundance of Pseudodactylogyrus spp. reduced this effect, but A. crassus was the strongest parasitic factor associated with fish behaviour, and abundance was positively related to delay in downstream passage. Delayed downstream migration at hydraulic gradients associated with riverine anthropogenic structures could result in additional energetic expenditure for migrating A. anguilla already challenged by A. crassus infection.